Diversity and antibiotic resistance in bacteria associated with symptoms of bacterial infection in Costa Rican crops - Uribe Lorío, Lorena (2024)
Objetive/Background. The aim of this was to assess the diversity and antibiotic resistance of bacteria isolated from 19 crops with bacterial infection symptoms. Material and Methods. This collection was identified using 16S rRNA gene sequencing and the Biolog system. Susceptibility and minimum inhibitory concentration (MIC) for streptomycin, tetracycline, and gentamicin were determined using disk diffusion and E-test methods, respectively. Results. A total of 55 species belonging to 20 bacterial genera were identified, with Pseudomonas, Serratia, Pantoea, and Stenotrophomonas being the most abundant. Approximately 27% of the isolates were categorized as pathogenic through the hypersensitivity reaction test, including phytopathogenic species like Pseudomonas syringae, P. cichorii, Pantoea anthophila, P. stewartii, Stenotrophomonas maltophilia, Dickeya oryzae, Erwinia billingiae, Pectobacterium aroidearum, and Enterobacter cloacae subsp. dissolvens. Resistance to at least one antibiotic was detected in 60% of isolates from 17 crops, with tomatoes, heart of palm, and lettuce exhibited the highest proportion of resistant bacteria (>80%). Streptomycin resistance was most common (35%), followed by tetracycline (28%) and gentamicin (9%). Conclusions. The findings indicate the presence of antibiotic resistance in saprophytic and pathogenic bacteria associated with 17 out of 19 assessed crops, posing risks to the environment, phytosanitary conditions, and public health.